How to Lower the Poverty?: Population Control and Increase of Asset Ownership - Sartika Djamaluddin (Signifikan: Jurnal Ilmu Ekonomi, 2017)
This study is intended to identify and analyze factors that influence the poverty rate in households in West Java. The study was carried out at three regional levels namely the provincial, district and municipal levels in West Java. This study used the model of logistic regression using the data from the national socioeconomic survey (Susenas) on household. The total number of households observed was 20.541 households. The findings indicate that control of total number of household members and asset ownership is the main factor that lowers the poverty rate in households in all regions. However factors that lower the probability of poverty in each district and municipality are varies. Another finding from the study is that financial aid from the community to support family spending is not always significant in lowering the probability of a household to be poor.DOI: 10.15408/sjie.v6i2.5096